Aktivitas dan Hasil Belajar Matematika Siswa dengan Penerapan Pembelajaran Talking Stick Media Teka Teki Silang - Amaliyah, Kholishotul; Yuliastuti, Rita; Nurfalah, Edy (FKIP Unirow Tuban, 2020)
The purpose of this study was to describe the increase in activities and student mathematics learning outcomes after the application of the Talking Stick Learning Model and Cross Puzzle Media were applied to the material on the Two Variable Linear Equation System. The results of this classroom action research analysis showed that student activity during the application of the Talking Stick learning model with crossword puzzle media had increased. This can be seen from the average student activity classically in the first cycle of 69.23%, the second cycle of 88.46% and the third cycle of 100%. Meanwhile, students' mathematics learning outcomes after the application of the Talking Stick learning model with crossword puzzle media had increased. This can be seen based on the test scores of students' mathematics learning outcomes in the application of the Talking Stick learning model with crossword puzzles media that have reached learning completeness. The average value of pre-cycle student learning outcomes with an average of 59.09 student learning outcomes with 25% classical learning completeness, cycle I with an average student learning outcomes of 60.84 with 38.46% classical learning completeness, cycle II with The average student learning outcomes of 92.30 with 100% classical learning completeness and cycle III with an average student learning outcomes of 98.60 with 100% classical learning completeness.